Evaluation of Accessibility of Iodinated Salt and Nutritional Iodine Status During Pregnancy - R Rostami; A Beiranvand; HR Khakhali; S Salary; MR Aghasi; J Nourooz-Zadeh (Tehran University of Medical Sciences, 2012)
Background: To assess accessibility of iodinated salt and urinary iodine concentrations (UIC) during pregnancy. This cross-sectional study was carried out between October and December, 2009 in Urmia County, West Azerbaijan (WA), Iran.Methods: Data on demographic characteristics and iodinated salt accessibility were gathered through a questionnaire at 1st trimester. Household salt samples and urine samples (1st -and 3rd trimesters) were analyzed for iodine content. Pregnant women (n=490) at 1st trimester were interviewed. Of these, 490 subjects (12 prenatal care centers) were enrolled.Results: All participants declared that they were exclusive users of iodinated salt. Segregation of the household salt samples according to iodine content (0, 8, 15 and 30 ppm) revealed that the respective distributions were 3.3%, 1.4%, 23.7% and 71.6%. Median UIC levels at 1st and 3rd trimesters were 73.5 µg/L and 114µg/L respectively. Accordingly, 86% and 70% of participants exhibited UIC < 150 µg/L.Conclusion: Median UIC during pregnancy in WA is markedly lower than those previously reported for regions with adequate iodine status in the country. Thus, extra iodine is needed to maintain adequate iodine store during gestation. In addition, this preliminary study reveals that a significant proportion (28%) of the household salt samples had low iodine content (≤ 15 ppm) although a level (>20 and <40 ppm) is mandatory in Iran. Further studies are deemed necessary to elucidate the cause(s) for manifestation iodine deficiency among pregnant women despite 20 years after iodine fortification strategy.